Maintenance electroconvulsive therapy for comorbid pharmacotherapy-refractory obsessive-compulsive and schizoaffective disorder - Hanisch F (European Journal of Medical Research, 2009)
Abstract Objective There is a high comorbidity of schizophrenia and obsessive-compulsory disorder (OCD) associated with more severe symptoms. Standard pharmacotherapy achieve symptom improvement in approximately 60% only. Results We report about a 48-old women treated for depression which developed successively psychotic symptoms (ideas of reference, psychotic worries), negative symptoms (blunted affect, impoverished thinking, difficulties in planning), and obsessive-compulsive symptoms (mainly repeating rituals, avoidance behaviour, collecting and hoarding). She did not respond to combined treatment with neuroleptics and high dose selective serotonin re-uptake inhibitors. She acutely improved during a course of electroconvulsive therapy (ECT) and was maintained on outpatient ECTs fortnightly together with 12 mg sertindol and 45 mg mirtazapine for 42 weeks. Conclusion Maintenance ECT is not an approved therapy in OCD but might be an option in pharmacotherapy refractory cases of comorbid OCD and schizophrenic/schizoaffective disorder.